New Security Challenges and the Need for New Forms of EU Cooperation: The Solidarity Declaration against Terrorism and the Open Method of Coordination - Ekengren, Magnus (European security (London, England), 2006)
The new transnational security threats, such as terrorism, challenge traditional methods of European Union cooperation. In the era of threats to inter-state peace the Union engendered security through 'passive' integration in the form of the abolition of European borders. Today the EU is increasingly given the responsibility for creating security and safety, both externally and internally, by the means of 'active' security instruments such as the European Security and Defence Policy and the Solidarity Declaration of 2004. The challenge is that these policies and principles require a vision beyond that of a free market, common threat perceptions and effective coordination of the crisis management capacity of EU member states. This article argues that the practical needs following this qualitative step, such as the strategic engagement of new security actors and levels of EU governance on a long term basis, are very similar to the ones that the Open Method of Coordination has attempted to resolve in EU cooperation in the field of welfare policies. It suggests that this method should be used also to strengthen the Union security policy and crisis management capacity.